F. L. Attenborough, The Laws of the Earliest English Kings 6-7 (Cambridge, UK: Cambridge University Press, 1922) (Transcription and translation of the Textus Roffensis,1 the Laws of Æthelberht, no. 18) - (:unkn) unknown (My University)
Prohibited supplying another with weapons while a quarrel is taking place. If no injury takes place, the lender shall pay a fine of six shillings.
Keywords: TRANSFER